Myocardial infarction with non-obstructive coronary arteries in a patient double-seropositive for anti-glomerular basement membrane and anti-neutrophil cytoplasmic antibodies: A case report - Krall, Marcell; Gollmer, Johannes; Pollheimer, Marion J.; Reiter, Clemens; Kolland, Michael; Kirsch, Alexander H.; Kronbichler, Andreas; Eller, Kathrin; Rosenkranz, Alexander R.; Odler, Balazs (Frontiers in Cardiovascular Medicine, 2022)
We report a case of a patient double-seropositive for anti-glomerular basement membrane (anti-GBM) and anti-neutrophil cytoplasmic antibodies (ANCA) who reported retrosternal chest pain during a regular hemodialysis session associated with ST-segment depression in electrocardiogram and an increase of serum high-sensitivity troponin T. Urgent coronary angiography excluded obstructive coronary artery disease, suggesting the diagnosis of ischemia with non-obstructive coronary arteries. This case illustrates an unusual presentation of cardiovascular involvement in a patient with double-positive ANCA/anti-GBM disease, emphasizing the possible relevance of coronary microvascular dysfunction and the need for close cardiovascular follow-up in this patient population.